The Anthropology of Ontology in Siberia: A Critical Review - Vaté, Virginie; Eidson, John R. (Anthropologica, 2022)
The dissolution of the Soviet Union opened a new phase in the anthropological study of Siberia, as researchers from Western Europe, North America, and Japan joined their colleagues of the former Soviet Bloc in the field. This occurred just as a number of new trends emerged in the field of anthropology, including those referred to as “the ontological turn” or “the anthropology of ontology.” To what extent could the latter, originally developed on the basis of research in Amazonia, be applied to Siberia? In this article, we offer a critical re-reading of contributions by some of the authors who have attempted to apply ontological perspectives to Siberian materials. The works we review include both comparative studies of the ontologies of different people, including Siberians, and ethnographies of particular Siberian communities. In conclusion, we illustrate certain criticisms that have been made of ontological approaches by examining how two of the authors under review – Philippe Descola and Rane Willerslev – have drawn on classic ethnographies of northeastern Siberia, particularly the works of Waldemar Bogoras on the Chukchi.